2017
DOI: 10.1016/j.sjbs.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abamectin and deltamethrin to the foragers honeybee workers of Apis mellifera jemenatica (Hymenoptera: Apidae) under laboratory conditions

Abstract: This study aimed at evaluating the toxicity of some insecticides (abamectin and deltamethrin) on the lethal time (LT) and midgut of foragers honeybee workers of were studied under laboratory conditions. The bees were provided with water, food, natural protein and sugar solution with insecticide (concentration: 2.50 ppm deltamethrin and 0.1 ppm abamectin). The control group was not treated with any kind of insecticides. The mortality was assessed at 1, 2, 4, 6, 12, 24, 48, and 72 hour (h) after insecticides tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
(44 reference statements)
0
12
0
4
Order By: Relevance
“…It most likely acts on GABA receptors by activation and blocking of the postsynaptic potential (Fritz et al 1979 ) and glutamate-gated chloride channels (Clark et al 1995 ). In bees, abamectin also affects cytotoxic midgut cells that may cause digestive disorders in the midgut; epithelial tissue is formed during morphological alterations when digestive cells die and is particularly dangerous for the foraging workers (Aljedani 2017 ). Cypermethrin applied at both plantations (AI of Cyperkill Super 25 EC) belongs to pyrethroids.…”
Section: Discussionmentioning
confidence: 99%
“…It most likely acts on GABA receptors by activation and blocking of the postsynaptic potential (Fritz et al 1979 ) and glutamate-gated chloride channels (Clark et al 1995 ). In bees, abamectin also affects cytotoxic midgut cells that may cause digestive disorders in the midgut; epithelial tissue is formed during morphological alterations when digestive cells die and is particularly dangerous for the foraging workers (Aljedani 2017 ). Cypermethrin applied at both plantations (AI of Cyperkill Super 25 EC) belongs to pyrethroids.…”
Section: Discussionmentioning
confidence: 99%
“…Some other research results showed that Abamectin indeed was highly effective in suppressing the population of Liriomyza (Ramesh and Ukey, 2007;Saad et al, 2007). Abamectin insecticide has caused the malfunction of some cells in those insects' digestion, more especially in the midgut (Aljedani, 2017). Abamectin application had decreased Liriomyza larvae significantly lower population of adult Liriomyza, spp.…”
Section: Abamectin Active Residuementioning
confidence: 99%
“…Type of insecticides that are commonly used by farmers contained Abamectin and Spinoteram active materials, working in contact, gastric and systemic that can cause cell malfunction in the insects' digestive tract, especially in the midgut (Aljedani, 2017;Srinivasa et al, 2014). Therefore, there is a need for pest management by applying broad-spectrum insecticide applications (Salvo and Valladares, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Secara umum jenis insektisida yang banyak diterapkan oleh petani, berbahan aktif Dimohipo, Curacron, Abamectin dan Spinoteram Arfan et al, 2018). Salah satu jenis insektisida dalam mengendalikan hama lalat pengorok daun yaitu Abamectin yang bekerja secara kontak, lambung dan sistemik (Srinivasa et al, 2014) menyebabkan tidak berfungsinya beberapa sel-sel pada bagian pencernaan serangga khususnya pada midgut (Aljedani, 2017 (Herlinda et al, 2005;Shahabuddin, 2012 di pertanaman bawang merah, yaitu ditemukan spesies Liriomyza spp sejak tanaman berumur masih berumur muda 2 MST-4 MST. Kondisi demikian diduga tanaman memiliki kandungan nutrisi yang dibutuhkan oleh imago dan larva (Herlinda et al, 2005) sedangkan pada umur tanaman 5-8 MST diduga terjadi pengerasan pada jaringan tanaman sehingga stilet tidak mampu mendukung dalam melakukan aktivitas makan.…”
Section: ------------------------------------------------------------unclassified
“…Kemampuan insektisida abamectin dalam menekan perkembangan larva Liriomyza, spp, hal ini mungkin disebabkan oleh cara kerja dari insektisida abamectin 18 EC bekerja secara kontak, lambung dan sistemik (Srinivasa et al, 2014). Penggunaan insektisida abamectin menyebabkan tidak berfungsinya beberapa sel-sel pada bagian pencernaan serangga khususnya pada midgut (Aljedani, 2017). dan juga bekerja dengan cara menghambat transmisi syaraf (Kola et al, 2015)…”
Section: ------------------------------------------------------------unclassified